I Married an Ebay Maniac - Jayne Perry (Indianapolis : USA Que, 2006)
Has your spouse been spending more and more time on the computer? Have new items been appearing in your house while your older possessions seem to disappear? Perhaps the explanation is in it - eBay mania! This title offers a glimpse into the world of eBay. It describes how to arrange a household to separate eBay from the non-eBay life.
Age Group: Adult
Includes index.
Keywords: Ebay; Internet auctions; Electronic commerce